Organizações não governamentais (ONGs) e mercado: estudo de campo de um inevitável choque de racionalidades - Lacerda, Daniel da Silva (2010)
What we have assumed as rational and logic from the beginning of the Modern Times provides a mental system, used on decision making, which carries itself a framework of premises and values. These rules aim the functional maximization of the consequences, far from any subjective value. Weber (1994) classified this system as 'instrumental rationality', distinguished as goal-oriented. He also defined the 'substantive rationality', assumed by the values of the subject and not oriented by any consequences of the action. Even though many authors started from these rationalities definitions to expose the duality that separates the world from the trends of market centralization and their instrumental logic, Guerreiro Ramos (1989) was the one who strongly contributed to the study of the organizations, separating different social enclaves, in which the rationalities would be better applied in one or another environment. In this context the marketplace although separated from others is an important and legitimated enclave where social relations are devoted to serve the subject. The present work is based on Critical Theory and assumes that the NGOs (NonGovernmental Organizations) belong to a different field from the one of economic organizations, once they are motivated by different rationalities. A field research was made among five nonprofit organizations, with declared goals of social action (Harmonicanto, Reviverde, ACAM, Observatório de Favelas and Bola pra Frente). The research aimed to identify deviating influences that the instrumental rationality imposes on the achievement of the original goals of these organizations. It was also observed that there are circumstances that support the adoption of the instrumental rationality, such as: necessity of self maintenance, the area of operation, the dimension of the organization, the influence of the leader, etc. The main outcome is that such organizations, despite the fact they are not environments dedicated to the individual’s growth (as the concept of Isonomy of Guerreiro Ramos defines), betray their public purpose, and are driven by the consequences every time they assimilate in a basic form the organizational dynamic of an economic organization.